Elderly Cognitive Functions at Tresna Werdha Islamic Village Nursing Home, Tangerang - Ratih Kumala Dewi (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2021)
Background: According to aging Index data in 2035, it is projected that there will be 73 elderly people per 100 population increasing every year. The implication of increasing the number of elderly is an increase in cognitive function degradation that affects the old age ratio dependency in carrying out normal daily activities. Objective: The purpose of this study was to determine the elderly cognitive functions at the Islamic Village Nursing Home. Methods:  This study used a cross-sectional study design with the sampling technique using a total population of 48 elderly woman respondents. The location of the research was carried out at the Islamic Village Nursing Home, Tangerang. Data collection was carried out in March to April 2020. Data was collected using a standard questionnaire for cognitive function measured using the standard Mini-Mental State Exam (MMSE) questionnaire and the level of independence measured using the standard Barthel Index checklist. Other respondent characteristic data were collected through interviews and observations. Results: Cognitive function has a significant relationship with the level of independence of elderly women with values (OR = 5.402; p = 0.013; CI = 95% 1.430 - 20.426). Elderly women with impaired cognitive function (MMSE score> 23) are at risk of experiencing a dependency level of 4.5 times in fulfilling daily activities compared to elderly women whose cognitive function is normal. Conclusion: The decline in cognitive function in the elderly is the biggest cause of the inability to carry out normal daily activities and also the most common reason for being dependent on others to take care of themselves. It is hoped that services at the nursing home, especially caregivers, can improve the quality of services for the elderly by increasing overall attention both by providing a holistic, comprehensive diagnostic effort, by paying attention to the role of the elderly so that the quality of life of the elderly can be improved.